2014
DOI: 10.1111/cod.12285
|View full text |Cite
|
Sign up to set email alerts
|

Positive patch test reactions to oxidized limonene: exposure and relevance

Abstract: Oxidized R-limonene is a common fragrance allergen, and limonene was frequently found in the labelling on the patients' products, and assessed as relevant for the patients' dermatitis. A large number of domestic and occupational sources for contact with R-limonene were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 39 publications
(68 reference statements)
6
39
0
Order By: Relevance
“…Investigations of clinical relevance of positive reactions among the patients identified rinse‐off products and essential oils as the most common sources of exposure to geraniol and citral (Table ). Although a small sample, this is in accordance with other studies on oxidized fragrance terpenes . In the European Union regulation, geraniol and citral are included in a group of 26 fragrance chemicals that must be labeled on cosmetic products in the European Union when used in concentrations greater than 10 ppm in leave‐on products and greater than 100 ppm in rinse‐off products, according to the Cosmetics Regulation .…”
Section: Discussionsupporting
confidence: 75%
“…Investigations of clinical relevance of positive reactions among the patients identified rinse‐off products and essential oils as the most common sources of exposure to geraniol and citral (Table ). Although a small sample, this is in accordance with other studies on oxidized fragrance terpenes . In the European Union regulation, geraniol and citral are included in a group of 26 fragrance chemicals that must be labeled on cosmetic products in the European Union when used in concentrations greater than 10 ppm in leave‐on products and greater than 100 ppm in rinse‐off products, according to the Cosmetics Regulation .…”
Section: Discussionsupporting
confidence: 75%
“…The high frequencies of reactions to oxidized fragrance compounds in clinical testing have turned the focus to potential haptens that are formed by air oxidation from far less sensitizing materials. The clinical relevance of these reactions has been discussed, and it has been shown that the patients, if questioned, will, in many cases, be using a product containing the mother compound on the dermatitis areas . For many individuals, the dermatitis will clear when such exposure is terminated .…”
Section: Discussionmentioning
confidence: 99%
“…In 14 patients, occupational contact dermatitis caused by limonene was determined [107]. Additionally, Christensson and co-workers [108] summarized clinical data on 2900 patch tested patients with dermatitis in Australia, Denmark, United Kingdom, Singapore, Spain and Sweden. The results showed that 149 patients reacted positive to oxidized limonene.…”
Section: Limonenementioning
confidence: 99%